THE ABILITY OF THE SECOND YEAR STUDENTS OF THE VOCATIONAL HIGH SCHOOL (SMK) TARUNA SATRIA PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Tarmizi Tarmizi; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was aimed to find out the Ability of the Second Year Students of the Vocational High School (SMK) Taruna Satria Pekanbaru in Comprehending Narrative Texts. The population of this research was the Second Year Students of the Vocational High School (SMK) Taruna Satria Pekanbaru. The number of sample was 32 students selected by using cluster random sampling technique. The research instrument was multiple choice questions consisted 30 questions. The test was given by using six components of reading comprehension of narrative texts such as specific information, moral value, main idea, reference, meaning of difficult word, and making inference of narrative text. The data were analyzed by classifying them into four levels of ability, such as poor, average, good, and excellent. The result showed that the ability of the second year students of the Vocational High School (SMK) Taruna Satria Pekanbaru was at good level with mean score was 65,2.Key Words: Students’ ability, Reading comprehension, Narrative text